1964
DOI: 10.2307/1539418
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte Measurements in Fishes Amphibia, and Reptiles

Abstract: Gulliver ( 1875) made an extensive study of the size of the red cells in vertebrates, extending over a period of years. Cullen (1903) gives values for the skate and dogfish, while Cleland and Johnston (1912) reported a considerable series, especially birds. Although Wintrobe (1961) tabulated the results of many investigators on red cell size, there have been relatively few reports of new red cell measurements and many species remain unreported.The size and shape of red cells gives an indication of the surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
40
0
2

Year Published

1973
1973
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 0 publications
7
40
0
2
Order By: Relevance
“…The erythrocyte dimensions in flamingos were very uniform in the four species analysed, but the results indicated that flamingo erythrocytes were slightly larger than those of most of the other avian species described in the literature (Hartman & Lessler, 1963;Palomeque & Planas, 1977. Nevertheless, birds are a very homogeneous group with respect to erythrocyte dimensions, particulary when compared with other vertebrate classes (Hartman & Lessler, 1964).…”
Section: Resultsmentioning
confidence: 72%
“…The erythrocyte dimensions in flamingos were very uniform in the four species analysed, but the results indicated that flamingo erythrocytes were slightly larger than those of most of the other avian species described in the literature (Hartman & Lessler, 1963;Palomeque & Planas, 1977. Nevertheless, birds are a very homogeneous group with respect to erythrocyte dimensions, particulary when compared with other vertebrate classes (Hartman & Lessler, 1964).…”
Section: Resultsmentioning
confidence: 72%
“…Thus, a small erythrocyte offers the possibility of a higher rate of exchange than a larger one (Hartman et al 1964;Sevinç et al 2000). According to Wintrobe (1933) the erythrocyte size reflects the position of a species on the evolutionary scale: in lower vertebrates and those with a not-so successful evolutionary past, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Ukuran dan bentuk sel eritrosit serta kandungan hemoglobin dapat mengindikasikan kemampuan respirasi hewan yang kemudian merupakan hasil adaptasi terhadap habitat yang berbeda (Hartman and Lessler, 1964).…”
Section: Pendahuluanunclassified
“…Data yang diperoleh kemudian ditampilkan dalam nilai rata-rata±standar deviasi. Hartman and Lessler (1964) yakni 27,9…”
Section: Prosedur Penelitianunclassified